Observation of V–V dimers softening and distinct length scales in nanostructured VO2 thin films - Ojha P.K.; Sharma R.; Hissariya R.; Babu S.; Ketkar E.; Singh S.; Neema S.; Rana A.; Pal N.; Sathe V.G.; Mishra S.K. (My University, 2025)
Employing temperature-controlled Raman spectroscopy, we demonstrate V–V dimers softening in nanostructured VO2 thin films. Temperature-dependent Raman band shifts and their spectral width (FWHM) suggest an intriguing phonon characteristic that evolves across the metal-insulator transition (MIT) during the heating/cooling thermal cycles. The V–V dimers start to collapse above a critical temperature (T > TMIT) and restoring their initial phase during the cooling process below TMIT. Raman bands suggest an abrupt reversible switching in the optical behaviour at a temperature (To = 332 K). Temperature-dependent sheet resistance variations indicate a smooth reversible resistive switching relatively at a lower temperature (Te = 340 K). The difference in transition temperatures has been discussed in the framework of light scattering cross-section from the metallic domains that become more extensive at the critical length scale required for percolation conduction in resistive switching. 2D-mean-field approximation associated with Mie scattering are modelled to explain the percolation process during phase transition and to estimate the metallic domain length scale evolved in the insulating matrix across the MIT. Our experimental findings explain the occurrence of optical and electrical transitions at the district temperature range, suggesting a weak coupling between lattice and optical switching. © 2022 Elsevier Ltd